The application in Spain of the Hispanic-Morocco Social Security Agreement under the light of the Euromediterranean Agreement and Regulation (EU) 1231/2010 - Sánchez-Rodas Navarro, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The Moroccan Hispanic Social Security Agreement is the oldest of the 24 Social Security Agreements concluded by Spain currently in force. Its material scope is restricted to the General Regime and to the Spanish Special Regimes that are expressly mentioned, not including the Special Regimes of Public Officials. It only applies to the Social Security contributory level, excluding unemployment benefits, benefits for cessation of activity and long-term care benefits. However, by application of the EuroMediterranean Agreement, which enshrines equal treatment in the field of Social Security for Moroccan workers and their families, they are entitled to non-contributory benefits and long-term care benefits. Moreover, Regulation (EU) 1231/2010 allows them to aggregate periods of insurance to be entitled to contributory and non-contributory Social Security benefits inside the territory of the European Union.
Keywords: Hispano-Moroccan Agreement; Euro-Mediterranean Agreement; Regulation (EU) 1231/2010; Social Security; long-Term Care